2014
DOI: 10.1055/s-0034-1383033
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers as Prognostic Factors in DCIS and Small Invasive Breast Cancers

Abstract: !Ductal carcinoma in situ (DCIS) accounts for up to half of screen-detected breast cancers and thus constitutes a major public health problem. Despite effective current treatment many patients with DCIS are either over-or undertreated because of the paucity of precise models to predict recurrence or progression. The combination of clinical and molecular factors as already applied for invasive disease may help to build such models also for DCIS. We compared 53 DCIS (36.6 %) and 92 (63.4 %) invasive breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…Support for the notion that breast cancer dissemination can occur in pre-invasive stages of tumour progression comes from the consistent finding of circulating tumour cells in the peripheral blood (or in the bone marrow) of patients with DCIS. In six studies (range 19–404 patients), between 13 and 25% of DCIS patients were found to have circulating tumour cells [ 29 34 ]. It has been proposed that such cells derive from an occult (micro)-invasive lesion within DCIS.…”
Section: Part 2: the Seer Study: Mortality After Dcismentioning
confidence: 99%
“…Support for the notion that breast cancer dissemination can occur in pre-invasive stages of tumour progression comes from the consistent finding of circulating tumour cells in the peripheral blood (or in the bone marrow) of patients with DCIS. In six studies (range 19–404 patients), between 13 and 25% of DCIS patients were found to have circulating tumour cells [ 29 34 ]. It has been proposed that such cells derive from an occult (micro)-invasive lesion within DCIS.…”
Section: Part 2: the Seer Study: Mortality After Dcismentioning
confidence: 99%
“…術後 3 年で多発肝骨肺転移を認めた非浸潤部 Her2 強陽性 DCIS の 1 例 聖隷佐倉市民病院乳腺外科 1) ,同 病理科 2) 黒 野 健 司 1) 川 島 太 一 1) 河 上 牧 夫 2) 症例は56歳,女性.健診にて DCIS ( Departments of Breast Surgery 1) and Pathology 2) , Seirei Sakura Citizen Hospital The case involved a 56-year-old woman who was diagnosed as having ductal carcinoma in situ (DCIS) at a medical check-up and underwent mastectomy + sentinel lymph node biopsy. Adjuvant chemotherapy was not selected.…”
Section: 症 例unclassified
“…5 Much controversy exists over the extent of treatment or if DCIS is a high-risk condition that only requires close follow-up despite potential future development of an invasive cancer. 12 Nomograms using breast cancer molecular markers 13 and multigene expression 14,15 as prognostic indicators show promise to predict the invasive component. [13][14][15] At the current time and until research yields decisive data, high-grade DCIS is surgically treated and, in the case of a lumpectomy, followed by radiation therapy to further reduce the risk that the lesion will recur either as DCIS or invasive disease.…”
Section: Breast Cancer Riskmentioning
confidence: 99%
“…12 Nomograms using breast cancer molecular markers 13 and multigene expression 14,15 as prognostic indicators show promise to predict the invasive component. [13][14][15] At the current time and until research yields decisive data, high-grade DCIS is surgically treated and, in the case of a lumpectomy, followed by radiation therapy to further reduce the risk that the lesion will recur either as DCIS or invasive disease. [12][13][14] Total or simple mastectomy provides for 90% risk reduction 16 without follow-up radiation therapy.…”
Section: Breast Cancer Riskmentioning
confidence: 99%
See 1 more Smart Citation